Characterisation of patients with severe asthma in the UK Severe Asthma Registry in the biologic era. Issue 3 (9th December 2020) - Jackson, David J; Busby, John; Pfeffer, Paul E; Menzies-Gow, Andrew; Brown, Thomas; Gore, Robin; Doherty, Martin; Mansur, Adel H; Message, Simon; Niven, Robert; Patel, Mitesh; Heaney, Liam G
Abstract : Background: The UK Severe Asthma Registry (UKSAR) is the world's largest national severe asthma registry collecting standardised data on referrals to UK specialist services. Novel biologic therapies have transformed the management of type 2(T2)-high severe asthma but have highlighted unmet need in patients with persisting symptoms despite suppression of T2-cytokine pathways with corticosteroids. Methods: Demographic, clinical and treatments characteristics for patients meeting European Respiratory Society / American Thoracic Society severe asthma criteria were examined for 2225 patients attending 15 specialist severe asthma centres. We assessed differences in biomarker low patients (fractional exhaled nitric oxide (FeNO) <25 ppb, blood eosinophils <150/μL) compared with a biomarker high population (FeNO ≥25 ppb, blood eosinophils ≥150/µL). Results: Age (mean 49.6 (14.3) y), age of asthma onset (24.2 (19.1) y) and female predominance (62.4%) were consistent with prior severe asthma cohorts. Poor symptom control (Asthma Control Questionnaire-6: 2.9 (1.4)) with high exacerbation rate (4 (IQR: 2, 7)) were common despite high-dose treatment (51.7% on maintenance oral corticosteroids (mOCS)). 68.9% were prescribed biologic therapies including mepolizumab (50.3%), benralizumab (26.1%) and omalizumab (22.6%). T2-low patients had higher body mass index (32.1 vs 30.2, p<0.001), depression/anxiety prevalence (12.3% vs 7.6%, p=0.04) and mOCS use (57.9% vs 42.1%, p<0.001). Many T2-low asthmatics had evidence of a historically elevated blood eosinophil count (0.35 (0.13, 0.60)). Conclusions: The UKSAR describes the characteristics of a large cohort of asthmatics referred to UK specialist severe asthma services. It offers the prospect of providing novel insights across a range of research areas and highlights substantial unmet need with poor asthma control, impaired lung function and high exacerbation rates. T2-high phenotypes predominate with significant differences apparent from T2-low patients. However, T2-low patients frequently have prior blood eosinophilia consistent with possible excessive corticosteroid exposure.